2013
DOI: 10.1080/15222055.2012.713896
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Diets Containing Standard Soybean Oil, Soybean Oil Enhanced with Conjugated Linoleic Acids, Menhaden Fish Oil, or an Algal Docosahexaenoic Acid Supplement on Channel Catfish Performance, Body Composition, Sensory Evaluation, and Storage Characteristics

Abstract: Fish consumption is a common method of obtaining beneficial n‐3 highly unsaturated fatty acids (LC‐PUFAs), but increased use of vegetable oils in fish diets to reduce dependence on fish oil dilutes the amounts of LC‐PUFAs. Conjugated linoleic acids (CLAs) are also considered beneficial for human health. Therefore, we investigated four different lipid sources in Channel Catfish Ictalurus punctatus diets for their ability to enhance fatty acid profiles of fillets to benefit human health while maintaining or impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Therefore, feeds for farmed fish need substantial amounts of these FAs [62]. Authors have shown that thraustochytrid oil or meal can be adequate alternatives to fish oil for cultured fish (e.g., [63,64,65,66,67]) or molluscs [68,69]. Live thraustochytrids have been used to enrich Artemia nauplii and rotifers before they are fed to fish larvae [70,71,72,73].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, feeds for farmed fish need substantial amounts of these FAs [62]. Authors have shown that thraustochytrid oil or meal can be adequate alternatives to fish oil for cultured fish (e.g., [63,64,65,66,67]) or molluscs [68,69]. Live thraustochytrids have been used to enrich Artemia nauplii and rotifers before they are fed to fish larvae [70,71,72,73].…”
Section: Discussionmentioning
confidence: 99%
“…Catfish. As CLA-rich oil has been shown to exert tissue incorporation in mammals, studies have been conducted on fish to investigate the accumulation of CLA in their tissues through dietary supplementation (Choi et al 1999, Faukner et al 2013. In a 175-day grow-out trial, channel catfish were fed a commercial 32% protein diet supplemented with 2% lipid from either CLA-rich soy oil produced by photoisomerization ( Jain et al 2008) or conventional soy oil.…”
Section: Beef and Lambmentioning
confidence: 99%
“…Some studies were a collaboration with economist/Center Director Dr. C. R. “Carole” Engle, who was running feeding trials with catfish to establish the most profitable production practices, and with the NWAC in Mississippi. Several trials were conducted involving the grow‐out of catfish, including investigating alternative feedstuffs (Engle, Kumar, Lochmann, Bosworth, & Thompson, ; R. Lochmann et al, ; R. T. Lochmann, Islam, Phillips, Adam, & Everette, ; Pugliese, Heikes, Engle, Bosworth, & Lochmann, ; Renukdas et al, ; Sink & Lochmann, ), prebiotics (Thompson, Lochmann, Phillips, & Sink, ), lipid sources (Faukner et al, , ; Sink & Lochmann, ; Suja, Lochmann, Sink, Phillips, & Chen, ), dietary protein and feeding frequency (Engle, Ruebush, Leyva, & Trimpey, ), and winter feeding (Bastola, Engle, Haukenes, & Freeman, ; Nanninga, Engle, Stone, & Goodwin, ). Research was also conducted on the nutrition of catfish fry (Sink, Lochmann, & Kinsey, ) and broodfish (Sink & Lochmann, ; Sink, Lochmann, Pohlenz, Buentello, & Gatlin, ).…”
Section: To Presentmentioning
confidence: 99%